2019
DOI: 10.11606/1807-0205/2019.59.08
|View full text |Cite
|
Sign up to set email alerts
|

Relative growth and population dynamics of Macrobrachium iheringi (Decapoda, Palaemonidae)

Abstract: During the ontogenetic development of crustaceans, the relative growth of some structures may change, especially during the transition from juvenile to adult. This study describes the relative growth of body structures of Macrobrachium iheringi, and provides information on its population dynamics, such as structure, fecundity, and morphological sexual maturity. The sampling of M. iheringi was carried out in “Ribeirão da Hortelã”, in Botucatu (SP, Brazil). The length of the carapace (CL), abdomen (AL), and isch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 43 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…Moraes‐Riodades and Valenti () suggested that the occurrence of morphotype differences s could be a characteristic of the genus Macrobrachium , and that this hypothesis could only be confirmed upon the examination of more species, because there are hundreds of species in the genus Macrobrachium . According to the current literature, M. iheringi ( Ortmann 1897) (Nogueira et al, ) and some populations of M. amazonicum from water reservoirs (e.g., Pantaleão et al, ; Paschoal, Oliveira, Andrioli, & Zara, ) do not seem to show this characteristic. Some species or populations may lack the differentiation, because differentiation may be driven by the production of peptides by the androgenic glands and regulated by other factors associated with the endocrine physiology of these animals (Paschoal & Zara, ; Rocha & Barbosa, ).…”
Section: Discussionmentioning
confidence: 96%
“…Moraes‐Riodades and Valenti () suggested that the occurrence of morphotype differences s could be a characteristic of the genus Macrobrachium , and that this hypothesis could only be confirmed upon the examination of more species, because there are hundreds of species in the genus Macrobrachium . According to the current literature, M. iheringi ( Ortmann 1897) (Nogueira et al, ) and some populations of M. amazonicum from water reservoirs (e.g., Pantaleão et al, ; Paschoal, Oliveira, Andrioli, & Zara, ) do not seem to show this characteristic. Some species or populations may lack the differentiation, because differentiation may be driven by the production of peptides by the androgenic glands and regulated by other factors associated with the endocrine physiology of these animals (Paschoal & Zara, ; Rocha & Barbosa, ).…”
Section: Discussionmentioning
confidence: 96%
“…The frequency distribution of males and females of M. brasiliense between the size classes followed a pattern, with a greater number of females in the smallest size classes and a greater number of males in the largest classes, which may be a reflection of the reproductive strategy called "temporary female guarding" (Bauer, 2004), with dominant males that court and protect females during copulation. This model of population structure seems to be a pattern in M. brasiliense, considering all the populations studied so far (Mantelatto and Barbosa, 2005;Pereira and Chacur, 2009;Oliveira et al, 2019), as well as for other Macrobrachium species (Mattos and Oshiro, 2009;Gualberto et al, 2012;Nogueira et al, 2019b;Perroca et al, 2021). Therefore, this type of sexual system appears to be common within the genus, since most populations are characterized by males being larger than females, with males showing aggressive behavior during social interactions (Fielder and Lee, 1983;Karplus et al, 1992;Karplus and Barki, 2019).…”
Section: Population Structure Of Macrobrachium Brasiliensementioning
confidence: 76%
“…The hypothesis that rainfall seasonality should affect population structure and reproduction leading to peak recruitment in the dry season was tested. This hypothesis is supported by the theory of upward (bottom-up) and downward (top-down) regulatory processes of population and community dynamics (Collar et al, 2017;Benke, 2018) and by several empirical studies that found a relationship between the reproductive period/recruitment with periods of greatest rainfall (Mantelatto and Barbosa, 2005;Nogueira et al, 2019b;Oliveira et al, 2019). The hypothesis proposes that: [1] different population structures occur between seasons (dry and rainy), i.e., immature and small individuals predominating in the dry season and a predominance of adult individuals and larger size classes in the rainy season; and [2] a significant relationship will occur between juvenile abundance and rainfall.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…and Penaeus spp. ( Bajaniya et al, 2014 ; Nogueira et al, 2019 ). Penaeus monodon also exhibits differential growth rate in which the female shows superior growth to male.…”
Section: Introductionmentioning
confidence: 99%